New Scopes, New Accessories, New Stents for Interventional Endoscopic Ultrasound - Christopher G. Chapman; Uzma D. Siddiqui (Korean Society of Gastrointestinal Endoscopy, 2016)
Technological advances have rapidly expanded the therapeutic potential of endoscopic ultrasound (EUS). Innovations in stent technology; directed adjunctive therapy for pancreatic tumors, including radiofrequency ablation and fiducial marker placement; advanced imaging modalities, including needle-based confocal laser endomicroscopy; and new echoendoscopes, such as the forward-viewing linear echoendoscope, are emerging as safe and effective tools and devices for providing a broad range of treatments and therapies previously not thought possible. In this review, we summarize and discuss the new echoendoscopes, accessories, and stents for interventional EUS and highlight the recent literature on technical and therapeutic efficacy. The therapeutic role and indications for EUS are rapidly evolving well beyond its current limits as new EUS-specific designed tools are designed, and ultimately, should help achieve the goal of improving patient outcomes.